A power waveform design based on OVSF-PPM for stress wave based wireless power transfer. (15th January 2021) - Zhang, Guangmin; Yang, Ping; He, Sihong; Zheng, Yu; Song, Gangbing
Highlights: The paper develops a power transfer waveform design for stress wave energy transfer. The proposed energy waveform is designed via the correlation analysis. The results demonstrate that the proposed waveform improves the ETE and the PAPR. Abstract: The lifetime of wireless sensors and devices is restricted by their limited battery capacities, since it is quite time-consuming and costly to replace batteries. Wireless power transfer is recognized as a feasible solution to charge wireless sensors and portable devices, since it can provide energy continuously for wireless electronic devices. This paper explores a waveform design for stress wave power transfer. In the proposed method, pulse position modulation (PPM) signals are firstly designed based on orthogonal variable spreading factor (OVSF) code. Then, power transfer waveforms for multiple receivers are created via analyzing the correlation among the PPM signals. When applied in stress wave power transfer, the proposed waveform is demonstrated to effectively improve power transfer performance at the intended receiver. We investigate three different transmission schemes, namely the pulse waveform, the time reversal waveform, and the proposed power transfer waveform, by comparing and analyzing their performances in experiments when one energy transmitter and one energy transfer array are respectively used. Due to multiple stress wave modes, rich dispersion and mutual interference among energy transfer signals, energy transfer efficiencies (ETE) and peak to average power ratios (PAPR) tend to be low by using pulse waveforms or traditional time reversal waveforms to transfer stress wave energy. On the contrary, by implementing the proposed waveform in stress wave power transfer, the ETE and the PAPR are effectively improved. In the experiment, three piezoceramic transducers mounted on a pipeline are used for stress wave power transfer. The experimental results demonstrate that the proposed waveform significantly improves the ETE and the PAPR, as compared with the other two waveforms.